2006
DOI: 10.1021/cb600431a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-Based Probe for the Analysis of Cathepsin Cysteine Proteases in Living Cells

Abstract: Mechanism-based probes are providing new tools to evaluate the enzymatic activities of protein families in complex mixtures and to assign protein function. The application of these chemical probes for the visualization of protein labeling in cells and proteomic analysis is still challenging. As a consequence, imaging and proteomic analysis often require different sets of chemical probes. Here we describe a mechanism-based probe, azido-E-64, that can be used for both imaging and proteomics. Azido-E-64 covalentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 53 publications
3
67
0
3
Order By: Relevance
“…The azide moiety is a unique chemical handle that permits selective coupling with bio-orthogonal phosphine or alkyne-derivatized reagents for detection and isolation by affinity purification for subsequent proteomic analysis. [33][34][35][36][37][38] The advantage of DAz-1 over existing probes for sulfenic acid detection is its small size, which contributes to its favorable uptake in cells and facilitates protein labeling. Moreover, once introduced into proteins the azide group can be tagged by a wide variety of affinity and fluorescent reagents ex vivo.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The azide moiety is a unique chemical handle that permits selective coupling with bio-orthogonal phosphine or alkyne-derivatized reagents for detection and isolation by affinity purification for subsequent proteomic analysis. [33][34][35][36][37][38] The advantage of DAz-1 over existing probes for sulfenic acid detection is its small size, which contributes to its favorable uptake in cells and facilitates protein labeling. Moreover, once introduced into proteins the azide group can be tagged by a wide variety of affinity and fluorescent reagents ex vivo.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the ability to 'tag' proteins with biotin or a range of other affinity and fluorescent reagents via the azide chemical reporter on DAz-1 provides an opportunity for enrichment and proteomic analysis of oxidized proteins. 33,34 These studies are currently underway and will be reported in due course. This new method to detect sulfenic acid-modified proteins provides a powerful means to detect changes in cysteine oxidation in vivo and should find a wide variety of applications for the study of biological processes that are central to human health and disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following precedents established by Cravatt and Speers [29], Overkleeft and coworkers [30], and Taunton and coworkers [31], Ploegh and coworkers recently demonstrated the use of an azido probe and the Staudinger ligation to visualize active cathepsins, an important class of cysteine proteases, in cells [32].…”
Section: Covalent Labeling Of Active Enzymesmentioning
confidence: 96%
“…These qualities make them valuable tools for cellular localization study [51,52] or activity analysis [53,99,100] of related proteins in intact cells once their targets become known. Besides, they are also helpful in understanding the roles of their targets in physiological and pathological processes.…”
Section: Other Application Of Activity Based Probes In Drug Discoverymentioning
confidence: 99%